USULAN PERBAIKAN SISTEM INVENTORI DI CAFÉ ABC UNTUK MEMINIMASI KERUGIAN DENGAN MEMPERHATIKAN EKSPEKTASI KEUNTUNGAN - Parama Kartika Dewa; Muflia Intan Putri; Hadi Santono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Café ABC is one of the MSMEs located in Yogyakarta and engaged in food. Café ABC is one of the MSMEs that produce food made from bananas. The banana fruit is then processed and becomes a satay banana krispi product with various flavor variants sold by Cafe ABC. The amount of erratic demand causes Cafe ABC outlets to often experience excess raw materials (Over Stock). The excess of raw materials occurs in the main raw materials, namely bananas that are always leftover or not exhausted. The Cafe ABC itself does not yet have a targeted amount of production and still uses an inventory control system based solely on estimates. The absence of production targets and inventory control on the CAFE ABC caused the outlet to experience a decrease in sales for 4 consecutive months. This causes revenue at Cafe ABC outlets to decrease, causing losses. The methodology used in this study is the Single Period Model or Newsboy Problem. The data used in the form of raw material purchase expenditure data, sales profit data, and banana satay sales data from March 2019 to February 2020. The result of the calculation of the use of the method is the proposed production target every week with Expected Profit. The prediction of the production target of week 2 was obtained as many as 394 skewers with an expected profit of Rp. 1,292,000. The prediction of the production target of week 3 was obtained as many as 380 skewers with an expected profit of Rp. 1,222,000. The prediction of the production target of week 4 was obtained as many as 379 skewers with an expected profit of Rp. 1,265,000.